2022
DOI: 10.3390/computers11080117
|View full text |Cite
|
Sign up to set email alerts
|

Combining Log Files and Monitoring Data to Detect Anomaly Patterns in a Data Center

Abstract: Context—Anomaly detection in a data center is a challenging task, having to consider different services on various resources. Current literature shows the application of artificial intelligence and machine learning techniques to either log files or monitoring data: the former created by services at run time, while the latter produced by specific sensors directly on the physical or virtual machine. Objectives—We propose a model that exploits information both in log files and monitoring data to identify patterns… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In previous work, we have focused on the detection of anomaly patterns by considering service log files and data coming from IT monitoring measurements, and leveraging natural language processing (NLP) solutions juxtaposed with multivariate time series anomaly detection techniques [1]. This study has revealed thousands of anomalies that have been verified by a comparison with the same log messages derived from the different services considered for the analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, we have focused on the detection of anomaly patterns by considering service log files and data coming from IT monitoring measurements, and leveraging natural language processing (NLP) solutions juxtaposed with multivariate time series anomaly detection techniques [1]. This study has revealed thousands of anomalies that have been verified by a comparison with the same log messages derived from the different services considered for the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This contribution brings work [1] further, exploring the statistical Z-score [2] and percentile [3] approaches, and Density-Based Algorithm for Discovering Clusters in Large Spatial Databases with Noise (DBSCAN) [4] in the anomaly detection field for time series numerical metrics related to IT and physical infrastructure sensors. The paper describes models defined by considering critical scenarios and a wide range and type of monitoring data.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from our initial study on log files aimed at building an anomaly dictionary and getting knowledge from files with the application of natural language processing (NLP) solutions and other ML techniques [1], we have continued combining a subset of log files and monitoring data information to detect anomaly patterns involving heterogeneous unstructured data [2]. NLP solutions have been applied to log files to identify anomalies from words and sequences of terms.…”
Section: Introductionmentioning
confidence: 99%